Supraventricular tachycardia and deep vein thrombosis following Moderna vaccination: A case series. Issue 3 (21st March 2023) - Bhandari, Niroj; Chaudhary, Aashutosh; Acharya, Suyash; Acharya, Shiwani Sharma; Paudel, Kusum; Karmacharya, Robin Man; Vaidya, Satish; Kunwar, Kajol; Bhatt, Swechha
Abstract: There have been reports of deep vein thrombosis and supraventricular tachycardia following the Moderna vaccination. The timing of SVT and DVT just after vaccination in our case series could suggest possible temporal relationships to the vaccination. But further studies are needed to establish such evidence. Abstract : We have reported supraventricular tachycardia and deep vein thrombosis following Moderna vaccination. The timing of the adverse effects was just after vaccination in our case series.